2021
DOI: 10.1007/s11442-021-1898-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent signal and impact of wet-to-dry climatic shift in Xinjiang, China

Abstract: The Xinjiang region of China is among the most sensitive regions to global warming. Based on the meteorological and hydrological observation data, the regional wet-to-dry climate regime shifts in Xinjiang were analyzed and the impacts of climatic shift on the eco-hydrological environment of Xinjiang were assessed in this study. The results showed that temperature and precipitation in Xinjiang have increased since the mid-1980s, showing a warming-wetting trend. However, drought frequency and severity significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…Previous studies have indicated that there are obvious differences in the characteristics of RSD for different rainfall rate classes (Bringi et al, 2003; Chen et al, 2017; Janapati et al, 2020; Ma et al, 2019; Tokay & Short, 1996). Xinjiang is located in the northwest of China, far away from the ocean, resulting in a continental arid climate (Huang et al, 2015; Yao et al, 2021). Considering the fact of high frequency of low rainfall rates in Xinjiang, the RSD data collected at Zhaosu and Tianchi are subdivided into five rainfall rate classes: R1: 0.1–0.5 mm h −1 , R2: 0.5–1 mm h −1 , R3: 1–3 mm h −1 , R4: 3–5 mm h −1 , R5: ≥5 mm h −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have indicated that there are obvious differences in the characteristics of RSD for different rainfall rate classes (Bringi et al, 2003; Chen et al, 2017; Janapati et al, 2020; Ma et al, 2019; Tokay & Short, 1996). Xinjiang is located in the northwest of China, far away from the ocean, resulting in a continental arid climate (Huang et al, 2015; Yao et al, 2021). Considering the fact of high frequency of low rainfall rates in Xinjiang, the RSD data collected at Zhaosu and Tianchi are subdivided into five rainfall rate classes: R1: 0.1–0.5 mm h −1 , R2: 0.5–1 mm h −1 , R3: 1–3 mm h −1 , R4: 3–5 mm h −1 , R5: ≥5 mm h −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Xinjiang is located in the northwest of China, far away from the ocean, resulting in a continental arid climate (Huang et al, 2015; Yao et al, 2021). The Tianshan Mountains in Xinjiang are known as the ‘Water Tower of Central Asia’.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, changes in the distribution of precipitation and drought in Northwest China have been noted in some studies 13 , 29 , 37 . In our study, the spatial center of precipitation in the arid region is used to analyze the changes, and the results show that the longitude of the spatial center of precipitation in the arid region presents a complex and continuous periodic change, while the latitude of the spatial center of precipitation in the arid region is relatively stable before 2000 and then began to fluctuate greatly.…”
Section: Discussionmentioning
confidence: 95%